Uterine bleeding with hormone therapies in menopausal women: a systematic review - J. H. Pickar; D. F. Archer; S. R. Goldstein; R. Kagan; B. Bernick; S. Mirkin (My University, 2020)
Uterine bleeding is a common reason why women discontinue menopausal hormone therapy (HT). This systematic review compared bleeding profiles reported in studies for continuous-combined HT approved in North America and Europe for moderate to severe vasomotor symptoms in postmenopausal women with a uterus. Non-head-to-head studies showed that uterine bleeding varies by formulation and administration route, with oral having a better bleeding profile than transdermal formulations. Cumulative amenorrhea over a year ranged from 18 to 61% with oral HT and from 9 to 27% with transdermal HT, as reported for continuous-combined HT containing 17β-estradiol (E2)/progesterone (P4) (56%), E2/norethisterone acetate (NETA) (49%), E2/drospirenone (45%), conjugated equine estrogens/medroxyprogesterone acetate (18–54%), ethinyl estradiol/NETA (31–61%), E2/levonorgestrel patch (16%), and E2/NETA patch (9–27%). Amenorrhea rates and the mean number of bleeding/spotting days improved over time. The oral E2/P4 combination was amongst those with lower bleeding rates and may be an appropriate alternative for millions of women seeking bioidentical HT and/or those who have bleeding concerns with other HT.
Keywords: Norethisterone acetate; Metrorrhagia; Levonorgestrel; Transdermal patch; Breakthrough bleeding; Norethisterone; Vasomotor; Drospirenone; Vaginal bleeding; Menopause: Health Impacts and Treatments